2021
DOI: 10.1016/j.radi.2020.05.011
|View full text |Cite
|
Sign up to set email alerts
|

Initial data from an experiment to implement a safe procedure to perform PA erect chest radiographs for COVID-19 patients with a mobile radiographic system in a “clean” zone of the hospital ward

Abstract: Introduction: With the current Covid-19 pandemic, general wards have been converted into cohort wards for Covid-19 patients who are stable and ambulant. A 2-radiographer mobile radiography team is required to perform bedside Chest X-rays (CXR) for these patients. Hospital guidelines require both radiographers to be in full Personal Protective Equipment (PPE) throughout the image acquisition process and the mobile radiographic unit needs to be disinfected twice after each case. This affects the efficiency of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 10 publications
0
15
0
3
Order By: Relevance
“…Thus, studies that use CT for grading include a disproportionate number of patients that undergo imaging due to either clinical deterioration or to exclude other reasons for hypoxia, such as pulmonary embolism. As such, CT is not as applicable for COVID-19 prognostication at the time of admission as CXR, which is widely available, inexpensive, and, in the case of portable CXR, more easily decontaminated (31)(32)(33). Lung ultrasound has also been explored as a method for diagnosing COVID-19 pneumonia, with at least one study demonstrating a higher specificity and sensitivity for lung ultrasound than for CXR (34).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Thus, studies that use CT for grading include a disproportionate number of patients that undergo imaging due to either clinical deterioration or to exclude other reasons for hypoxia, such as pulmonary embolism. As such, CT is not as applicable for COVID-19 prognostication at the time of admission as CXR, which is widely available, inexpensive, and, in the case of portable CXR, more easily decontaminated (31)(32)(33). Lung ultrasound has also been explored as a method for diagnosing COVID-19 pneumonia, with at least one study demonstrating a higher specificity and sensitivity for lung ultrasound than for CXR (34).…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…One study showed that the image quality was rated as uniformly excellent when the technique was used on a phantom but did not evaluate this imaging technique on patients. 10 Brady and colleagues reported that 30 through-glass radiographs were assessed by 2 readers: one scored 70% of them as acceptable quality while the other scored 90% of them acceptable. 11 However, they did not compare these images to conventionally obtained radiographs.…”
Section: Discussionmentioning
confidence: 99%
“…Radiografer telah mengupayakan optimisasi: kualitas citra dan dosis radiasi citra dengan pemilihan faktor eksposi yang disesuaikan dengan kondisi pasien dan memaksimalkan post processing untuk meningkat kualitas. Kesimpulan: Dalam melakukan upaya optimisasi pada sistem pencitraan CR perlu pemahaman tentang EI, hal ini berkaitan tentang kategori underexposed, optimal dan overexposed, selain itu radiografer dapat memanfaatkan post PENDAHULUAN Pada saat pandemi COVID-19, pencitraan radiografi menjadi salah satu diagnosa screening pada pasien suspect COVID-19, untuk pasien dewasa dan anak-anak yang kooperatif dapat dilakukan dengan pemeriksaan Posterior Anterior (PA) (Sng et al, 2020) (Woznitza et al, 2020). Pencitraan radiografi dada (CXR) memiliki peran penting dalam membantu diagnosis dan perkembangan perawatan pada pasien COVID-19.…”
Section: A B S T R a Kunclassified